Fortification performance of polyurethane coating in outdoor historical ironworks - Reda, Y. (2023)
The results confirmed that the decorative ironworks were manufactured from wrought and gray cast iron. The main corrosion products identified by XRD are goethite, akageneite, and maghemite. Lead oxide hydrate refers to old lead paints (red primer) which have been applied to protect the ironworks. Quartz and calcite are the products of heavy dust particles that covered the surface.